Marketing Strategies to Promote Event Marketing and MICE Business Research Under the New Society, Social Distancing Economy, According to the New Normal Economic Model, Tourism Study, Nakhon Si Thammarat Province - Khumhaeng, Supatra (Siam University Journal of Business Administration, 2025)
The objective of the research is to study tourism factors. Study satisfaction and study the marketing mix of MICE tourism business management in Nakhon Si Thammarat Province. Purposive sampling used convenience sampling. Data were analyzed using descriptive statistics. Frequency breakdown Percentages and standard deviations and inferential statistical analysis. Tourism factors found that tourism for rewards Travel only with family/relatives Vehicle is a personal car. Traveling members 1-5 people, duration 2-3 days, cost 9,001 - 12,000 baht. Overall tourist satisfaction is at a high level ( = 4.23) (S.D. = 0.94). It was found that the image, distinctiveness, location / reputation of the place There is an efficient working system. Complete facilities There are enough parking places. It is safe. Marketing mix, MICE business management The overall picture was at the highest level ( = 4.17) (S.D. = 0.41). It was found that the products and places were safe. Marketing promotion Effective media is used to reach the target group thoroughly. Personnel are professional in organizing activities and in physical appearance. There are staff available to provide service throughout the duration of the activity. Marketing strategies to promote event marketing and MICE business management of Nakhon Si Thammarat province tourism under the new society, Social Distancing Economy, according to the New Normal economic model, that is, knowing the needs of consumers. Improve service quality Making a difference in service Build identity and pride in your community through creative thinking. Using online media and marketing communications to create awareness, good management and communication planning, plans to operate in the same direction and create awareness.